Flood damage and risk assessment for urban area in Segamat - Noor Suraya, Romali (2018)
In recent years, risk-based flood mitigation approach received more attention compared to conventional or structural approach. However, in developing countries, literatures on flood vulnerability assessment are limited especially on flood damage. In Malaysia, the assessment of flood damages is challenging due to data scarcity. Hence, an attempt has been made to establish a flood damage assessment framework for an urban area of Segamat town, Johor. The concept of flood risk involved the elements of hazard, exposure, and vulnerability. The combination of hydrological characteristics, exposed elements, value of exposed elements, and flood damage function curve was used for estimation of flood damages. The flood depth and areal extend were obtained from flood modeling and mapping using HEC-HMS/RAS and Arc GIS. A site-specific flood depth–damage curve was developed based on land use category, socio-economic status of the flood victims and property characteristics. Due to data scarcity, synthetic method was applied to generate flood damage data based on the 2011 major flood event. Damage percentage was calculated by dividing the replacement cost by the market value of the properties and plotted against the observed flood depth. In addition to flood depth, the flood damage was also influenced by household income and property’s price. Therefore, the residential category was further divided into three sub-categories; low price house (LPH), medium price house (MPH) and high price house (HPH). Using R2 of 0.76 for commercial area and from 0.80 to 0.85 for various residential categories, the flood depth-damage curves obtained in this study were good enough and comparable with other studies. The estimated total damages for residential and commercial categories during the 2011 flood were RM456 mil and RM143 mil respectively. The expected annual damage (EAD) for residential areas (50,112 units) and commercial areas (9,318 premises) were RM12.59 million and RM2.96 million respectively. Generalized Pareto (GP) distribution model was used to estimate peak discharge of 10, 25, 50, 100, 200, 500 and 1000 ARI which were subsequently applied for deriving flood maps. Based on the GP distribution, the 2011 flood was equivalent to 42 years average recurrence interval (ARI). Flood hazard map shows that Bandar Seberang area (46,184 properties) was the most affected by flood. The flood damage risk map illustrates similar patterns where the distribution of damages were concentrates at the Bandar Seberang area with some properties suffered damages of more than RM15,000 per unit. Although it is a site-specific study, the framework can be applied to assess the potential future damages and serve as a basis for future studies on flood risk assessment in Malaysia.